PENGARUH IKLAN TELEVISI DAN CITRA MEREK TERHADAP KESADARAN MEREK SERTA DAMPAKNYA PADA KEPUTUSAN PEMBELIAN AIR MINUM DALAM KEMASAN MEREK LE MINERALE DI KOTA PEKANBARU - Marhamah Umi; Restuti Sri; Nursanti Aida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aimed to analysze Television Advertising and Brand Imageon Brand Awareness and Purchase Decision, research applied on consumers whohave seen and bought an unknown amount of Le Minerale water. This researchconsist of four variables: one dependent variable, one intervening variable andtwo independent variables. They are Employees Purchase Decision (Y2), BrandAwareness (Y1), Brand Image (X2), and Television Advertising (X1). Thisresearch was conducted using a sample of 120 people. This research useporposing sampling method that mean sample depends on some criteria. In termsdata analysis, this research used path analysis method using SPSS (StatisticalPackage for Social Science) version 25. Based on the hypothesis test conducted,research show that Television Advertising and Brand Image has simultaneousand partial significant positive effect on Brand Awareness, Television Advertisingand Brand Image has simultaneous and partial significant positive effect onPurchase Decision, Brand awareness has has a positive and significant effect onPurchase Decision, Television Advertising and Brand Image has a positive andsignificant effect on Purchase Decision are moderated by Brand Awareness. Keywods: Television Advertising, Brand Image, Brand Awareness, PurchasingDecision.